The Arctic Journey:Design Experiments in the North - Miettinen, Satu; Jylkäs, Titta (Springer Open, 2017)
Arctic journey was an experiential exhibition series that was realized as a part of HumanSee research project at the University of Lapland in 2016. The exhibition series seeked to experiment the multisensory ways of presenting personal experiences in the Arctic and to invite exhibition visitors into the co-creation of the installations. By exploring the exhibition formats, this article asks what is the role of co-design process in the construction of an arctic experience. Two of the exhibition cases included co-creation sessions, where the creation of the arctic experience was taken into a closer experimentation through the co-design process. Through qualitative content analysis and discourse analysis, the research findings suggest that arctic experience, even when not connected to personal experiences in the actual arctic region, is a reflection of the personal understanding of the marginal context that brings the stories of an individual into the core of the experience.